Cover Feature: Delineation of the Critical Parameters of Salt Catalysts in the N‐Formylation of Amines with CO2 (Chem. Eur. J. 47/2019). Issue 47 (8th July 2019) - Hulla, Martin; Ortiz, Daniel; Katsyuba, Sergey; Vasilyev, Dmitry; Dyson, Paul J.
Abstract : N‐formylation of amines with CO2 is base‐catalyzed and studies of salt catalysts reveal that the reaction is efficiently catalyzed by "free" floating anions of high basicity, as represented in the cover image. More information can be found in the Full Paper by P. J. Dyson et al. onpage 11079 .